IMPLEMENTATION OF VIDEO SELFIE TECHNIQUE TO REDUCE STUDENT LEARNING DEVIANT BEHAVIOR - Murni, Afrida (UNIB Press, 2016)
Abstract: This research is a classroom action reaserch, which aims to reduce the deviation of student learning behavior in PPKN class subjects while showing normal behavior during learning process by applying Vidio Selfie Technique in class X KC1 SMKN 3 Kota Bengkulu. This study took place in two cycles. The first cycle was held in three meetings. The second cycle was four meetings. The learning method used in class action is cooperative learning method with Selfie Video Technique. The average of student behavior change in cycle one is 73,12%. Increased 23.95% from pre cycle data of 49.17%. In the second cycle increased 13.89% to become 87.01%. Observations were made on four subjects: PPKn, Islamic Education, History Education and Indonesian Language. The results showed that the application of Selfie Video Technique can reduce the deviation of student